2005
DOI: 10.1523/jneurosci.2086-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Synaptic Metaplasticity Requires Inhibitory Autophosphorylation of Ca2+/Calmodulin-Dependent Kinase II

Abstract: Virtually all CNS synapses display the potential for activity-dependent long-term potentiation (LTP) and/or long-term depression (LTD).Intriguingly, the potential to exhibit LTP or LTD at many central synapses itself is powerfully modulated by previous synaptic activity. This higher-order form of plasticity has been termed metaplasticity. Here, we show that inhibitory autophosphorylation of Ca 2ϩ / calmodulin-dependent kinase II (CaMKII) is required for hippocampal metaplasticity at the lateral perforant path-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 46 publications
2
48
1
Order By: Relevance
“…Previous analysis of mouse mutants has revealed that abnormalities in expression of glutamate receptors and intracellular signal transducing molecules, such as the nonreceptor tyrosine kinase fyn, Ca 2ϩ /calmodulin-dependent protein kinase II, postsynaptic density-95, and neurogranin lead to metaplastic changes in the hippocampus (Mayford et al, 1995;Kiyama et al, 1998;Lu et al, 1999;Migaud et al, 1998;Krucker et al, 2002;Huang et al, 2004;Zhang et al, 2005). Here, we have discovered an extracellular matrix molecule involved in metaplasticity.…”
Section: Discussionmentioning
confidence: 78%
“…Previous analysis of mouse mutants has revealed that abnormalities in expression of glutamate receptors and intracellular signal transducing molecules, such as the nonreceptor tyrosine kinase fyn, Ca 2ϩ /calmodulin-dependent protein kinase II, postsynaptic density-95, and neurogranin lead to metaplastic changes in the hippocampus (Mayford et al, 1995;Kiyama et al, 1998;Lu et al, 1999;Migaud et al, 1998;Krucker et al, 2002;Huang et al, 2004;Zhang et al, 2005). Here, we have discovered an extracellular matrix molecule involved in metaplasticity.…”
Section: Discussionmentioning
confidence: 78%
“…A likely candidate to mediate metaplasticity processes was suggested to be an autophosphorylated state of calcium/calmodulin kinase II (CaMKII) (Bear, 1995;Mayford et al, 1995;Giese et al, 1998). In particular, autophosphorylation at site Thr305/306 has a suppressive effect on the calmodulin kinase binding, acting on a very slow timescale as described in our model (Elgersma et al, 2002;Zhang et al, 2005). The phosphorylation state at these sites has been shown recently to play a pivotal role in the induction of LTP and LTD, thus being an ideal candidate for the regulation of the BCM sliding threshold (Pi et al, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…43). Moreover, it has been demonstrated that priming-induced Thr305/306 phosphorylation prevents subsequent LTP induction (32). In these examples, threshold shifts follow prior synaptic activity; thus, they constitute forms of metaplasticity as predicted by the BCM rule.…”
Section: Discussionmentioning
confidence: 99%
“…Negative regulation of CaMKII by Thr305/ 306 autophosphorylation requires prior calcium/calmodulin-mediated activation of CaMKII and subsequent calmodulin dissociation (31). Moreover, it has been shown that Thr305/306 phosphorylation, triggered by 10-Hz priming, reduces hippocampal LTP (32), whereas genetic manipulation of the Thr305/306 phosphorylation site lowers the LTP threshold and prevents priming (27,32). Thus, CaMKII inhibitory autophosphorylation depends on previous calcium signaling and directly affects the kinase/phosphatase balance, thus fulfilling the two requirements outlined above.…”
Section: Significancementioning
confidence: 99%